Development and validation of a cross-cultural capital scale for international academic sojourners - Sehrish Nawaz; Riaz, Muhammad Naveed; Riaz, Muhammad Akram (Journal of International Students, 2026)
This research addresses the critical need for a psychometrically sound instrument to assess the multifaceted construct of cross-cultural capital among international academic sojourners. The main objective of the study was to develop and validate the cross-cultural capital scale for academic sojourners. Through rigorous qualitative (e.g., interviews with international students) and quantitative methods (e.g., exploratory and confirmatory factor analyses, reliability and validity assessments against related constructs such as cultural intelligence and ethnocentrism), the scale’s dimensionality was established using data collected from a diverse sample of academic sojourners across various host cultures. Finally, four factors were extracted, including cross-cultural skills, cross-cultural attitudes, cross-cultural knowledge, and cross-cultural belief. The resulting scale is expected to provide researchers and practitioners with a valuable tool for understanding the role of cross-cultural capital in academic success, intercultural adjustment, and overall well-being among academic sojourners.